Japan's ODA and Philippine saving and growth - Mapalad, Maria Claret M. (The Philippine Review of Business and Economics, 2000)
This paper assesses the impact of Japan's ODA on Philippine saving and growth over the period of 1956-95 using regression and simulation methods. The approach taken here reflects a deliberate attempt to correct for specific weaknesses in the existing literature on economic assistance and its impact on the recipient country. In particular, the study focuses on a one donor-one recipient relation, employs systematic quantitative methods, and takes account of the role of policy environment in the recipient country. This paper finds that Japan's ODA over the 40 years span complemented Philippine saving and increased income growth. The TSLS model finds no support for the possibility that Japan's ODA was simply substituting for Philippine saving, while the simulation model finds Japan's ODA generated additional income for the Philippines. This paper also highlights the importance of complementarity between private and public sector investments in the Philippines, with Japan's ODA providing significant funding for the latter.